2009
DOI: 10.1002/mrd.21094
|View full text |Cite
|
Sign up to set email alerts
|

E.E. Just's “independent irritability” revisited: The activated egg as excitable soft matter

Abstract: Ernest Everett Just's experimental work on post-fertilization events in invertebrate eggs led him to posit a dynamic and directive role for the zygotic "ectoplasm" (cortical cytoplasm), in subsequent development. His perspective was neglected during the years that followed his early death not only because of his well-documented marginalization as an African-American in U.S. science, but because his ideas were at odds with the growing gene-centrism of developmental biology in the latter half of the 20th century… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 89 publications
1
9
0
Order By: Relevance
“…DPMs that refer to individual cell functions such as the POLs and OSC, are to be understood as designating the multicellular consequences of those functions (Based on Newman and Bhat 2008. See Newman and Bhat 2008, 2009 connection between evolution and development has led us to conclusions at odds with the Modern Synthesis, though our framework finds support from findings by investigators working within Evo-devo employing different paradigms from ours: (i) Morphological evolution does not necessarily track genetic evolution; largescale morphological change can occur with a minimum of genetic change, while morphology can be static despite extensive genetic change (e.g., Kuraku and Meyer 2008;Cardoso et al 2009) (ii) Phenotypic change can precede associated genotypic change (e.g., WestEberhard 2003;Palmer 2004). (iii) Macroevolutionary change can be very rapid (e.g., Rokas et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DPMs that refer to individual cell functions such as the POLs and OSC, are to be understood as designating the multicellular consequences of those functions (Based on Newman and Bhat 2008. See Newman and Bhat 2008, 2009 connection between evolution and development has led us to conclusions at odds with the Modern Synthesis, though our framework finds support from findings by investigators working within Evo-devo employing different paradigms from ours: (i) Morphological evolution does not necessarily track genetic evolution; largescale morphological change can occur with a minimum of genetic change, while morphology can be static despite extensive genetic change (e.g., Kuraku and Meyer 2008;Cardoso et al 2009) (ii) Phenotypic change can precede associated genotypic change (e.g., WestEberhard 2003;Palmer 2004). (iii) Macroevolutionary change can be very rapid (e.g., Rokas et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…D'Arcy Wentworth Thompson (1860Thompson ( -1948 suggested that viscous flow and environmentally induced mechanical deformation, among other physical factors, could explain the shapes of organisms and morphological transformations between different species (Thompson 1942). The embryologist E. E. Just described the animal egg as a purely physical system that was nonetheless "self-acting, self-regulating and self-realizing" (Just 1939, 237;Newman 2009). One implication of these views-that much biological form was nonadaptive-had no place in the emerging standard model, however, and these figures were relegated to the scientific margins during their lifetimes.…”
mentioning
confidence: 99%
“…All that was needed to activate the egg and initiate the developmental process, then, was a stimulus, either a spermatozoon or a nonspecific trigger (hypertonic or hypotonic seawater, UV light, temperature change), which would set in motion a whole series of events that was latent in the system. (See Newman () for a description of some of the ways in which changes at the egg's surface during fertilization influence or determine later events taking place in the embryo.) The cell was poised and ready to be triggered by these nonspecific stimuli.…”
Section: The Just–holtfreter Connectionmentioning
confidence: 99%
“…William Bateson (1861Bateson ( -1926 proposed that certain tissues exhibited oscillatory excitations that could cause them to organize into segmental and other repeating patterns (Bateson and Bateson 1928;Newman 2007). The embryologist E. E. Just described the animal egg as a purely physical system that was nonetheless "self-acting, self-regulating and self-realizing" (Just 1939, 237;Newman 2009). The embryologist E. E. Just described the animal egg as a purely physical system that was nonetheless "self-acting, self-regulating and self-realizing" (Just 1939, 237;Newman 2009).…”
Section: What Is Still Missing In the Current Practicementioning
confidence: 99%